Earn-outs to bridge gap between negotiation parties – curse or blessing? - Toll, Christian; Rolinck, Jan-Philipp (Managerial Economics, 2017)
An agreement upon the terms of company transactions is aggravated by the existence of different information levels concerning the negotiation parties; this can be seen as a basic cause for divergent price expectations. Hence, the question is how the existing differences in price expectations of the transaction parties can be handled to reach a consensus, even when there is no area of agreement in the initial round of negotiations. Earn-outs are an interesting approach in overcoming divergent price expectations by making the purchase price dependent on the future performance of the company. However, formulating and implementing earn-outs may have a substantial potential for conflict. The present contribution shows which advantages and disadvantages the transaction parties face if an agreement regarding earn-outs is made.